Preparation method of fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet, composite board and preparation method and application of composite board
By combining solvent-free hot coating process with high-temperature resistant adhesive resin, the problems of uneven fiber impregnation and low interface bonding strength in PPS-based composite materials were solved, and high-performance, recyclable fiber cloth reinforced polyphenylene sulfide alloy composite plates were prepared, which are suitable for new energy vehicles and aerospace structures.
Patent Information
- Application Number
- CN202510932601.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-07
- Publication Date
- 2025-09-05
AI Technical Summary
The existing production of PPS-based composite materials has problems such as uneven fiber impregnation, high porosity, poor interlayer bonding, low interface bonding strength, and difficulty in balancing toughening and heat resistance, resulting in high production costs, poor environmental protection, and performance defects.
The solvent-free hot coating process is used in conjunction with high-temperature resistant adhesive resin. The PPS powder is mixed with the second component colloid in the medium temperature zone and then hot-coated on the surface of the fiber cloth. The prepreg sheet is then hot-laminated to achieve uniform impregnation and high-strength bonding of the fiber cloth.
A fiber cloth reinforced polyphenylene sulfide alloy composite plate with high density, high mechanical properties and recyclability was prepared. It is environmentally friendly, meets green manufacturing standards, has better performance than traditional thermosetting composite materials, and is suitable for new energy vehicles and aerospace fields.
Smart Images

Figure CN120588531A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of manufacturing electrical component assemblies, and in particular to a method for preparing a fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet, a composite board, and a preparation method and application thereof. Background Art
[0002] Thermoplastic composites, with their advantages of recyclability, high damage tolerance, and short molding cycles, are gradually replacing traditional thermoset composites in sectors such as aerospace, new energy vehicles, and electronic packaging. Fiber-reinforced high-performance thermoplastic composites are expected to account for over 30% of the global thermoplastic composites market by 2025. Compared to thermosets, thermoplastic composites can be recycled by melting and then adding a plastic matrix to reshape the material.
[0003] Among them, polyphenylene sulfide (PPS), a semi-crystalline specialty thermoplastic engineering plastic, combines excellent thermal stability, chemical resistance, and low moisture absorption, making it an ideal matrix for the preparation of lightweight, high-strength composite materials. Furthermore, as a thermoplastic resin, PPS can achieve 100% recycling of composite materials through melt processing, avoiding the environmental pollution issues associated with thermoset composites. PPS / carbon fiber composites can achieve a specific strength over three times that of aluminum alloys and exhibit excellent fatigue resistance. However, pure PPS resin is significantly brittle. When composites are subjected to impact loads, the matrix is prone to brittle cracking. Despite the superior performance of PPS-based composites, due to limitations in their production process, only Ensinger, a German company, currently commercializes high-quality products worldwide. These products are widely used in high-performance load-bearing components in aerospace and other fields in multiple countries. Accelerating the process of domestically produced substitution of these products is imperative.
[0004] Its industrial application is still limited by the following core issues.
[0005] Currently, the melt impregnation process is the most mature PPS-based prepreg process developed by manufacturers and researchers. However, the high viscosity of PPS melts makes it difficult to fully wet the fiber woven fabric during the traditional melt impregnation process. This high viscosity of the PPS melt leads to uneven fiber impregnation, resulting in high porosity and poor interlayer adhesion within the composite material. Existing technologies use high-temperature and pressure impregnation, which can partially improve the situation but is prone to thermal oxidation yellowing of PPS, and the process is energy-intensive and requires high equipment requirements.
[0006] In addition to the melt impregnation method, powder impregnation is a process method commonly used in the production of PPS composite materials, which is divided into wet and dry methods. Among the powder impregnation methods, the wet method requires multiple solvent treatment processes, and has problems such as poor environmental protection, residual micropores, and uneven powder dispersion due to dependence on solvents. The dry method relies on precision fluidized bed equipment. Both of these lead to a high increase in production costs. In addition, the powder in the dry process has problems such as poor fluidity, insufficient fiber penetration depth, and fiber damage and matrix aging caused by high temperature and high pressure. In addition, the interface bonding between PPS powder and fiber is poor, and there is a lack of chemical bonding. The poor adhesion of the powder leads to higher processing difficulty, high process complexity, limited matrix toughening, and uneven adhesion, resulting in large defects in the performance of the composite material. Summary of the Invention
[0007] In view of this, a method for preparing a solvent-free, recyclable, environmentally friendly, low-energy-consuming, and overall tough fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet, a composite board, and a preparation method and application thereof are provided. Through the synergistic effect of an innovative hot coating process and a high-temperature resistant adhesive resin, key technical difficulties such as uneven fiber impregnation caused by the high viscosity of the PPS melt, pore defects caused by solvent residues, low interfacial bonding strength, and difficulty in balancing toughening and heat resistance are solved, and finally a high-performance PPS-based fiber cloth composite board with high density, high mechanical properties, and recyclability is obtained.
[0008] A method for preparing a fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet comprises the following steps: A1) Pulverizing polyphenylene sulfide; PPS resin particles are pulverized into fine powder by a pulverizing process, and the pulverized powder is sieved through a sieving machine to obtain PPS powder of a predetermined particle size; A2) Mixing a polyphenylene sulfide alloy: PPS powder, a second component colloid, and an additive are added to a mixing device, and mixed within a predetermined medium temperature range for a predetermined time to obtain a polyphenylene sulfide alloy blend, wherein the medium temperature range is 100-250°C, the second component colloid is an adhesive thermosetting resin or an adhesive thermoplastic polyvinylidene fluoride resin, and the second component colloid has a viscosity of ≤10,000 mPa·s within the medium temperature range of 100-250°C, and an initial thermal decomposition temperature of greater than 300°C; A3) Prepreg of fiber cloth by hot coating: The reinforcing fiber cloth is passed through the hot coating head of a multi-layer hot melt coating device via a traction system. The blended rubber obtained in step A2) is conveyed to the hot coating head via the hot melt coating device. The coating temperature is controlled within a predetermined medium temperature range and coated on both sides of the reinforcing fiber cloth. The prepreg is then compacted using a roller device at a predetermined pressure roller temperature to allow the rubber to penetrate into the gaps between the fiber bundles, thereby forming a prepreg sheet. In this step, the medium temperature range is 100-250°C, and the predetermined pressure roller temperature is 50-150°C.
[0009] Preferably, the volume ratio of the polyphenylene sulfide powder to the second component colloid is 60-80%:20-40%.
[0010] Preferably, the second component colloid is one or a combination of two or more of thermosetting epoxy resin, silicone resin, polyimide, acrylic resin, phenolic resin, cyanate resin, amino resin, or one or a combination of two or more of thermoplastic polyvinylidene fluoride resin, polyamide resin, polypropylene resin, polyethylene resin. Preferably, the reinforcing fiber cloth is at least one of carbon fiber cloth, glass fiber cloth, basalt fiber cloth, aramid fiber cloth, poly(p-phenylene benzobisoxazole) fiber cloth, poly(arylene oxadiazole) fiber cloth, and ultra-high molecular weight polyethylene fiber cloth.
[0011] Preferably, the mixed material in step A2) further includes an inorganic reinforcing component; the mass of the inorganic reinforcing component is 0-20% of the sum of the mass of the polyphenylene sulfide powder and the second component colloid; the inorganic reinforcing component is one or a mixture of two or more of carbon black, carbon fiber staples, carbon nanotubes, silica, zirconium dioxide, boron nitride, silicon nitride, boron carbide, silicon carbide, talc, aluminum oxide, calcium carbonate, etc.
[0012] Preferably, the second component colloid is a compound of one or two or more of epoxy resin, silicone resin and phenolic resin; the auxiliary agent includes at least one of a cross-linking agent, an antioxidant and a compatibilizer; the mass of the auxiliary agent is 0.5-5% of the total mass of the blended rubber.
[0013] Preferably, the pulverization process in step A1) is one of mechanical pulverization and freeze pulverization; the D50 of the PPS powder after screening is 5-50 μm; and the mixing process in step A2) can be one of internal mixing, open mixing, and screw continuous extrusion.
[0014] In another aspect, the present invention further provides a method for preparing a fiber cloth reinforced polyphenylene sulfide alloy composite plate, which comprises the following steps: B1) Cutting and Laminating Prepregs; Prepregs of polyphenylene sulfide alloy are obtained according to the above-described method for preparing fiber cloth reinforced polyphenylene sulfide alloy prepregs, and the prepregs of polyphenylene sulfide alloy are cut into sizes corresponding to the hot pressing mold by a cutting device. After cutting, the prepregs are stacked in layers of 2 to 1000 layers; B2) Hot lamination: After forming the prepreg sheets, the prepreg sheets are stacked and placed in a hot lamination mold. The lamination equipment temperature is raised to the high temperature range, preheated at a pressure of 0.5-2 MPa for 1-60 minutes, and then hot pressed. The pressure is maintained at a pressure of 2-25 MPa for 10-600 minutes. The high temperature range is 250-350°C. B3) Cooling and cooling; maintaining the molding pressure to cool down, and opening the mold after the temperature drops below 150° C. to obtain a fiber cloth reinforced polyphenylene sulfide alloy composite plate.
[0015] In another aspect of the present invention, a fiber cloth reinforced polyphenylene sulfide alloy composite plate is provided, which comprises a multilayer polyphenylene sulfide alloy prepreg formed by stacking and hot laminating. The hot lamination method is to stack multiple layers of polyphenylene sulfide alloy prepreg prepared according to the fiber cloth reinforced polyphenylene sulfide alloy prepreg preparation method as described above and then hot press them. The hot pressing conditions are: preheating at a high temperature range of 250-350°C at a pressure of 0.5-2 MPa for 1-60 minutes, and then maintaining the pressure at a pressure of 2-25 MPa for 10-600 minutes.
[0016] Furthermore, a fiber cloth-reinforced polyphenylene sulfide alloy composite plate is provided for use in new energy vehicle battery covers, overall vehicle chassis, and aerospace structural components.
[0017] The above-mentioned fiber cloth reinforced polyphenylene sulfide alloy prepreg preparation method, composite board and preparation method thereof have at least the following beneficial effects: by crushing the PPS resin into powder form and mixing it with the second component colloid, the composite colloid after mixing has good thermal fluidity in the medium temperature region greater than 80°C to realize the solvent-free hot coating and impregnation process of the fiber cloth, and a fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet and its composite board are prepared by a subsequent stacking and hot pressing process. This product not only realizes the solvent-free environmentally friendly hot coating process, but also improves the overall toughness of the PPS-based composite board by introducing the second component colloid into the structural composition of the composite board. Different from the thermosetting composite board that currently accounts for a large proportion of the market, it is a thermoplastic recyclable material, which does not conflict with the existing environmental protection policies of my country, the European Union and other countries. It is a high-performance environmentally friendly alternative product for existing new energy vehicle battery covers, overall vehicle chassis, and aerospace structural components. In addition, the above-mentioned fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet and composite board also have the following advantages: a1. This invention innovatively introduces a second colloid component into the polyphenylene sulfide (PPS) resin system that is high-strength, heat-resistant, and exhibits excellent fluidity and adhesion in the medium-temperature range. This component not only serves as a dispersion carrier for the PPS powder, enabling a solvent-free hot coating process, but also acts as a second organic phase to form a homogeneous alloy with PPS, synergistically optimizing material properties. This combined design effectively mitigates the inherent brittleness of pure PPS resin and significantly enhances its impact strength. a2. Traditional wet processes rely on toxic solvents such as NMP, and solvent recovery energy consumption accounts for 20% to 30% of total energy consumption, making them less environmentally friendly. In contrast, the present invention uses a solvent-free hot coating process, completely avoiding the use and residue issues of solvents, with VOC emissions approaching zero, meeting green manufacturing standards and offering significant advantages in terms of environmental friendliness and production safety. a3. Compared to mature thermosetting composite materials such as sheet molding compound (SMC) and epoxy fiberglass boards, the product in this application offers significant advantages. Its high thermoplastic content and low thermosetting content allow for efficient recycling through crushing and melting, while also exhibiting superior mechanical properties. This makes it a high-performance, recyclable thermoplastic composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The present invention provides a flow chart of a method for producing a composite board from fiber cloth reinforced polyphenylene sulfide alloy prepreg sheets. DETAILED DESCRIPTION
[0019] The present invention will be described in detail below with reference to specific embodiments and accompanying drawings.
[0020] See also Figure 1 , showing a process for preparing a fiber cloth reinforced polyphenylene sulfide alloy composite plate, the method first prepares a fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet, and the preparation method of the fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet includes the following steps: A1) Pulverizing polyphenylene sulfide; PPS resin particles are pulverized into fine powder by a pulverizing process, and the pulverized powder is sieved through a sieving machine to obtain PPS powder of a predetermined particle size; A2) Mixing a polyphenylene sulfide alloy: PPS powder, a second component colloid, and an additive are added to a mixing device, and mixed within a predetermined medium temperature range for a predetermined time to obtain a polyphenylene sulfide alloy blend, wherein the medium temperature range is 100-250°C, the second component colloid is an adhesive thermosetting resin or an adhesive thermoplastic polyvinylidene fluoride resin, and the second component colloid has a viscosity of ≤10,000 mPa·s within the medium temperature range of 100-250°C, and an initial thermal decomposition temperature of greater than 300°C; A3) Prepreg of fiber cloth by hot coating: The reinforcing fiber cloth is passed through the hot coating head of a multi-layer hot melt coating device via a traction system. The blended rubber obtained in step A2) is conveyed to the hot coating head via the hot melt coating device. The coating temperature is controlled within a predetermined medium temperature range and coated on both sides of the reinforcing fiber cloth. The prepreg is then compacted using a roller device at a predetermined pressure roller temperature to allow the rubber to penetrate into the gaps between the fiber bundles, thereby forming a prepreg sheet. In this step, the medium temperature range is 100-250°C, and the predetermined pressure roller temperature is 50-150°C.
[0021] Preferably, the pulverization process in step A1) is one of mechanical pulverization and freeze pulverization. Further preferably, the PPS resin particles are pulverized using a cryogenic airflow mill, with nitrogen gas at -100 to -50°C being introduced to control the temperature during the process. Preferably, the D50 of the PPS powder after sieving in step A1) is 5-50 μm. Further preferably, the D50 of the polyphenylene sulfide powder after sieving in step A1) is 5-15 μm.
[0022] In step A2), the volume ratio of the polyphenylene sulfide powder to the second component colloid is preferably 60-80%:20-40%.
[0023] Preferably, the second component colloid is one or more of a thermosetting epoxy resin, silicone resin, polyimide, acrylic resin, phenolic resin, cyanate resin, and amino resin, or a combination of two or more thereof, or a thermoplastic polyvinylidene fluoride resin, polyamide resin, polypropylene resin, and polyethylene resin. The resin used in the second component colloid has fluidity and plasticity within the medium temperature range of 100-200°C, and its thermal decomposition temperature is greater than 300°C. It will not decompose and cause product defects during subsequent hot lamination in the high temperature range.
[0024] More preferably, the second component colloid is a compound of one or two or more of epoxy resin, silicone resin and phenolic resin, which provides excellent plasticity and fluidity for the overall rubber compound in the medium temperature range, and its polar groups can more effectively bond the PPS powder and reinforcing fibers, while ensuring less impact on the heat resistance of the PPS-based overall board.
[0025] Preferably, the reinforcing fiber cloth, also known as reinforcing fiber woven cloth, is preferably at least one of carbon fiber cloth, glass fiber cloth, basalt fiber cloth, aramid fiber cloth, poly(p-phenylene benzobisoxazole) fiber cloth, poly(arylene oxadiazole) fiber cloth, and ultra-high molecular weight polyethylene fiber cloth. Furthermore, carbon fiber woven cloth is preferred, as it has a higher modulus and lower density overall, making it suitable for use in high-performance lightweight structural products.
[0026] Preferably, the mixed material in step A2) further includes an inorganic reinforcing component, which is a commercially available inorganic filler that can be used in a polymer composite material system; the mass of the inorganic reinforcing component is 0-20% of the sum of the mass of the polyphenylene sulfide powder and the second component colloid; the inorganic reinforcing component is preferably one or a mixture of two or more of carbon black, carbon fiber staples, carbon nanotubes, silica, zirconium dioxide, boron nitride, silicon nitride, boron carbide, silicon carbide, talc, aluminum oxide, calcium carbonate, etc.
[0027] Preferably, the auxiliary agent includes at least one of a cross-linking agent, an antioxidant, and a compatibilizer; the mass of the auxiliary agent is 0.5-5% of the total mass of the blended rubber.
[0028] Preferably, the pulverization process in step A1) is mechanical pulverization or freeze pulverization; the D50 of the PPS powder after screening is 5-50 μm; and the mixing process in step A2) can be one of internal mixing, open mixing, or continuous screw extrusion. Further preferably, the mixing process uses internal mixing, which, through high shear and kneading within a closed cavity, can thoroughly mix the PPS powder and the second component colloid. This high-intensity mechanical shear effectively breaks down powder agglomerates, reduces interfacial defects, and improves the mechanical properties of the composite material. The pressure roller temperature in step A3) is preferably 70-150°C.
[0029] Another aspect of the present invention provides a method for preparing a fiber cloth reinforced polyphenylene sulfide alloy composite plate, which includes the following steps.
[0030] B1) Cutting and Laminating Prepregs: A polyphenylene sulfide alloy prepreg is obtained according to the above-described method for preparing a fiber cloth-reinforced polyphenylene sulfide alloy prepreg. The polyphenylene sulfide alloy prepreg is cut into a size corresponding to the hot pressing mold using a cutting device. The prepregs after cutting are then stacked in layers of 2 to 1000 layers. By controlling the number of layers, composite board products of a range of thicknesses can be precisely produced, preferably 10 to 1000 layers.
[0031] B2) Hot Lamination: After forming the prepreg sheets, the prepreg sheets are stacked and placed in a hot lamination mold. The temperature of the lamination equipment is raised to the high temperature range, and the preheating is carried out at a pressure of 0.5-2 MPa for 1-60 minutes before hot pressing. The pressure is maintained at a pressure of 2-25 MPa for 10-600 minutes. The high temperature range of the hot lamination is preferably 280-320°C.
[0032] B3) Cooling: Maintaining the molding pressure to cool down the material. After the temperature drops below 150°C, the mold is opened to obtain a fiber cloth reinforced polyphenylene sulfide alloy composite plate.
[0033] Therefore, another aspect of the present invention further provides a fiber cloth-reinforced polyphenylene sulfide alloy composite plate, comprising multiple layers of polyphenylene sulfide alloy prepreg sheets formed by stacking and then hot-laminating. The hot-lamination method comprises stacking multiple layers of polyphenylene sulfide alloy prepreg sheets prepared according to the above-described fiber cloth-reinforced polyphenylene sulfide alloy prepreg preparation method, followed by hot pressing. The hot pressing conditions are: preheating at a high temperature range of 250-350°C, at a pressure of 0.5-2 MPa for 1-60 minutes, and then maintaining the pressure at 2-25 MPa for 10-600 minutes. The specific process and conditions for forming the fiber cloth-reinforced polyphenylene sulfide alloy composite plate are described above and will not be repeated here.
[0034] In addition, embodiments of the present invention also provide a fiber cloth-reinforced polyphenylene sulfide alloy composite sheet for use in new energy vehicle battery covers, integral vehicle chassis, and aerospace structural components. Specifically, the heat-laminated fiber cloth-reinforced polyphenylene sulfide alloy composite sheet is further processed through molding, vacuum forming, and other processes to produce a high-performance, environmentally friendly, recyclable product for use in new energy vehicle battery covers, integral vehicle chassis, and aerospace structural components.
[0035] The following uses multiple examples to illustrate various aspects such as the preparation method of fiber cloth reinforced polyphenylene sulfide alloy prepreg sheets and composite boards, as well as the test results of the prepreg performance.
[0036] Example 1 The PPS resin particles are crushed by a cryogenic air flow mill, and cold nitrogen is introduced to control the temperature. After the crushing, the powder is sieved through a sieving machine to obtain fine powder with a particle size of less than 15um for standby use.
[0037] 2899g PPS powder, 533.8g bisphenol A epoxy resin, 336.9g phenolic epoxy resin, 230.1g methyl phenyl silicone resin, 120g nano alumina, 40g silane coupling agent KH550, 12g plastic lubricant KJ-B109, and 20g antioxidant 1076 were added to a mixing device and mixed at 150°C and 35rpm for 30min; a back pressure of 0.6MPa was applied during the mixing process to obtain a polyphenylene sulfide alloy blend.
[0038] A 0.2mm-thick T700-grade carbon fiber plain weave fabric is pulled through the hot-coating head of a multi-layer hot-melt coating machine. The hot-coating barrel is heated to 180°C, and the blended rubber is conveyed through a screw-driven hot-melt coating machine to the hot-coating head, where it is coated on both sides of the carbon fiber fabric. The fabric is then compacted through a three-roll mill at a 100°C roller temperature to produce a 0.35mm-thick polyphenylene sulfide alloy prepreg sheet.
[0039] The polyphenylene sulfide alloy prepreg sheets were cut into sizes suitable for the hot pressing mold using a cutting machine. After cutting, the prepreg sheets were stacked in 15 layers. After stacking, the layers were placed in a hot lamination mold. The lamination machine was heated to 290°C and preheated at 0.5 MPa for 5 minutes before hot pressing. The pressure was then maintained at 15 MPa for 300 minutes. The mold was opened after the temperature dropped below 150°C to produce a fiber cloth-reinforced polyphenylene sulfide alloy composite panel with a thickness of 4.4 mm.
[0040] Example 2 The PPS resin particles are crushed by a cryogenic air flow mill, and cold nitrogen is introduced to control the temperature. After the crushing, the powder is sieved through a sieving machine to obtain fine powder with a particle size of less than 15um for standby use.
[0041] 2896.5g of PPS powder, 729.5g of bisphenol F epoxy resin, 374g of epoxy-modified silicone resin, 120g of nano-silica, 40g of silane coupling agent KH550, 12g of plastic lubricant KJ-B109, and 20g of antioxidant 1076 were added to a mixing device and mixed at 150°C and 35rpm for 30min; a back pressure of 0.6MPa was applied during the mixing process to obtain a polyphenylene sulfide alloy blend.
[0042] A 0.2mm-thick T700-grade carbon fiber plain weave fabric is pulled through the hot-coating head of a multi-layer hot-melt coating machine. The hot-coating barrel is heated to 150°C, and the blended rubber is conveyed through a screw-driven hot-melt coating machine to the hot-coating head, where it is coated on both sides of the carbon fiber fabric. The fabric is then compacted through a three-roll mill at a roller temperature of 100°C to produce a 0.32mm-thick polyphenylene sulfide alloy prepreg sheet.
[0043] The polyphenylene sulfide alloy prepreg sheets were cut into sizes suitable for the hot pressing mold using a cutting machine. After cutting, the prepreg sheets were stacked in 15 layers. After stacking, the layers were placed in a hot lamination mold. The lamination machine was heated to 290°C and preheated at 0.5 MPa for 10 minutes before hot pressing, which was then maintained at 15 MPa for 300 minutes. The mold was then opened while the temperature was lowered to below 150°C, resulting in a 4.2mm thick fiber cloth-reinforced polyphenylene sulfide alloy composite panel.
[0044] Example 3 The PPS resin particles are crushed by a cryogenic air flow mill, and cold nitrogen is introduced to control the temperature. After the crushing, the powder is sieved through a sieving machine to obtain fine powder with a particle size of less than 15um for standby use.
[0045] 2598g of PPS powder, 1402g of propargyl phenolic resin, 120g of nano-silica, 40g of hexamethylenetetramine, 40g of silane coupling agent KH550, 12g of plastic lubricant KJ-B109, and 20g of antioxidant 1076 were added to a mixing device and kneaded at 130°C and 35rpm for 30 min; a back pressure of 0.6MPa was applied during the kneading process to obtain a polyphenylene sulfide alloy blend.
[0046] A 0.2mm-thick T700-grade carbon fiber plain weave fabric is pulled through the hot-coating head of a multi-layer hot-melt coating machine. The hot-coating barrel is heated to 150°C, and the blended rubber is conveyed through a screw-driven hot-melt coating machine to the hot-coating head, where it is coated on both sides of the carbon fiber fabric. The fabric is then compacted through a three-roll mill at a roller temperature of 100°C to produce a 0.32mm-thick polyphenylene sulfide alloy prepreg sheet.
[0047] The polyphenylene sulfide alloy prepreg sheets were cut into sizes suitable for the hot pressing mold using a cutting machine. After cutting, the prepreg sheets were stacked in 15 layers. After stacking, the layers were placed in a hot lamination mold. The lamination machine was heated to 300°C and preheated at 0.5 MPa for 15 minutes before hot pressing, which was then maintained at 15 MPa for 240 minutes. The mold pressure was maintained while the temperature was lowered to below 150°C. The mold was then opened to produce a fiber cloth-reinforced polyphenylene sulfide alloy composite panel with a thickness of 4.2 mm.
[0048] Example 4 The PPS resin particles are crushed by a cryogenic air flow mill, and cold nitrogen is introduced to control the temperature. After the crushing, the powder is sieved through a sieving machine to obtain fine powder with a particle size of less than 15um for standby use.
[0049] 2909g PPS powder, 1091g bisphenol A epoxy resin, 120g nano-silica, 40g silane coupling agent KH550, 12g plastic lubricant KJ-B109, and 20g antioxidant 1076 were added to a mixing device and kneaded at 150°C and 35rpm for 30 min; a back pressure of 0.6MPa was applied during the kneading process to obtain a polyphenylene sulfide alloy blend.
[0050] A 0.2mm-thick T700-grade carbon fiber plain weave fabric is pulled through the hot-coating head of a multi-layer hot-melt coating machine. The hot-coating barrel is heated to 180°C, and the blended rubber is conveyed through a screw-driven hot-melt coating machine to the hot-coating head, where it is coated on both sides of the carbon fiber fabric. The fabric is then compacted through a three-roll mill at a 100°C roller temperature to produce a 0.36mm-thick polyphenylene sulfide alloy prepreg sheet.
[0051] The polyphenylene sulfide alloy prepreg sheets were cut into sizes suitable for the hot pressing mold using a cutting machine. After cutting, the prepreg sheets were stacked in 14 layers. After stacking, the layers were placed in a hot lamination mold. The lamination machine was heated to 300°C and preheated at 0.5 MPa for 15 minutes before hot pressing, which was then maintained at 15 MPa for 240 minutes. The mold was opened while the temperature was maintained until it dropped below 150°C, resulting in a fiber cloth-reinforced polyphenylene sulfide alloy composite panel with a thickness of 4.3 mm.
[0052] Example 5 The PPS resin particles are crushed by a cryogenic air flow mill, and cold nitrogen is introduced to control the temperature. After the crushing, the powder is sieved through a sieving machine to obtain fine powder with a particle size of less than 15um for standby use.
[0053] 2555.8g of PPS powder, 1444.2g of polyvinylidene fluoride, 120g of nano-alumina, 24g of anti-hydrolysis agent carbodiimide, 40g of silane coupling agent KH550, 12g of plastic lubricant KJ-B109, and 20g of antioxidant 1076 were added to a mixing equipment and kneaded at 190°C and 35rpm for 30 min; a back pressure of 0.6MPa was applied during the kneading process to obtain a polyphenylene sulfide alloy blend.
[0054] A 0.2mm-thick T700-grade carbon fiber plain weave fabric is pulled through the hot-coating head of a multi-layer hot-melt coating machine. The hot-coating barrel is heated to 210°C, and the blended rubber is conveyed through a screw-driven hot-melt coating machine to the hot-coating head, where it is coated on both sides of the carbon fiber fabric. The fabric is then compacted through a three-roll mill at a roller temperature of 100°C to produce a 0.35mm-thick polyphenylene sulfide alloy prepreg sheet.
[0055] The polyphenylene sulfide alloy prepreg sheets were cut into sizes suitable for the hot pressing mold using a cutting machine. After cutting, the prepreg sheets were stacked in 15 layers. After stacking, the layers were placed in a hot lamination mold. The lamination machine was heated to 300°C and preheated at 0.5 MPa for 15 minutes before hot pressing. The pressure was then maintained at 15 MPa for 180 minutes. The mold was opened while the temperature was lowered to below 150°C, resulting in a 4.5mm thick fiber cloth-reinforced polyphenylene sulfide alloy composite panel.
[0056] After seven days of heat treatment and natural aging to eliminate self-crosslinking, the products from Examples 1 to 5 were subjected to performance testing. These included interlaminar shear strength testing (ISO 14129), tensile testing (ISO 527), and flexural testing (ISO 14125).
[0057] Table 1 Fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet performance test results
[0058] The above data demonstrates that the composite panels prepared in Examples 1 and 2 exhibit superior overall performance. Both systems utilize a combination of epoxy resin and silicone. The polar groups of the epoxy resin form a strong interfacial bond with the PPS powder and fiber surface, significantly enhancing interlayer adhesion. The addition of silicone resin (Examples 1 and 2) further improves colloid fluidity and heat resistance, facilitating rubber penetration between fiber bundles. Furthermore, the coordinated flow windows of the epoxy and silicone resins in the mid-temperature range match, ensuring the rubber's fluidity and penetration into the interfiber gaps while minimizing the impact of high temperatures on performance.
[0059] Comparing Example 1 with Example 4, the expected synergistic effect of epoxy and silicone is that the epoxy resin provides adhesion, while the silicone improves flexibility and heat resistance. However, the interlaminar shear strength of the composite (128 MPa) is significantly higher than that of Example 4 (121 MPa), which uses only epoxy resin. Furthermore, the flexural strength (790 MPa) is 23% higher than that of Example 4 (640 MPa). The silicone's flexible chains mitigate the epoxy's brittleness, while its siloxane bonds enhance high-temperature stability, creating a "rigid and flexible" interface structure.
[0060] In Example 5, the interlaminar shear strength (89 MPa) of PVDF, used as the bonding component, was significantly lower than that of the thermosetting colloid formulation (107–128 MPa), and the flexural strength (620 MPa) was the lowest. This is likely due to the fact that PVDF has too low a viscosity at the lamination temperature (300°C) (its thermal decomposition temperature is greater than 300°C, but its fluidity is too high), causing the adhesive to be squeezed out of the interfiber gaps, thereby reducing density. Furthermore, PVDF lacks reactive groups and cannot form chemical bonds with the fibers, relying solely on physical forces, resulting in weak interfacial bonding.
[0061] It should be noted that the present invention is not limited to the above-mentioned embodiments. Based on the creative spirit of the present invention, those skilled in the art can also make other changes. These changes made based on the creative spirit of the present invention should be included in the scope of protection required by the present invention.
Claims
1. A method for preparing a fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet, characterized in that: The following steps are involved: A1) Pulverizing polyphenylene sulfide; PPS resin particles are pulverized into fine powder by a pulverizing process, and the pulverized powder is sieved through a sieving machine to obtain PPS powder of a predetermined particle size; A2) Mixing a polyphenylene sulfide alloy: PPS powder, a second component colloid, and an additive are added to a mixing device and mixed for a predetermined time within a predetermined medium temperature range to obtain a polyphenylene sulfide alloy blend, wherein the medium temperature range is 100-250°C, the second component colloid is an adhesive thermosetting resin or an adhesive thermoplastic resin, the second component colloid is a resin having fluidity and plasticity within the medium temperature range of 100-200°C, the thermal decomposition temperature of the second component colloid is greater than 300°C, the viscosity of the second component colloid within the medium temperature range of 100-250°C is ≤10,000 mPa·s, and the initial thermal decomposition temperature is greater than 300°C; A3) pre-impregnation of the fiber cloth with hot coating; the reinforcing fiber cloth is passed through the hot coating head of a multi-layer hot melt coating device via a traction system, and the blended rubber obtained in step A2) is conveyed to the hot coating head through the hot melt coating device, the coating temperature is controlled within a predetermined medium temperature range, and the reinforcing fiber cloth is coated on both sides; Subsequently, the prepreg is compacted by a rolling device at a predetermined roller temperature to allow the rubber to penetrate into the gaps between the fiber bundles to form a prepreg sheet. The medium temperature range in this step is 100-250°C, and the predetermined roller temperature is 50-150°C.
2. The method for preparing a fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet according to claim 1, wherein: The volume ratio of the polyphenylene sulfide powder to the second component colloid is 60-80%:20-40%.
3. The method for preparing the fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet according to claim 1, wherein: The second component colloid is one or a combination of two or more of thermosetting epoxy resin, silicone resin, polyimide, acrylic resin, phenolic resin, cyanate resin, and amino resin, or one or a combination of two or more of thermoplastic polyvinylidene fluoride resin, polyamide resin, polypropylene resin, and polyethylene resin.
4. The method for preparing a fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet according to claim 1, wherein: The reinforcing fiber cloth is at least one of carbon fiber cloth, glass fiber cloth, basalt fiber cloth, aramid fiber cloth, poly(p-phenylene benzobisoxazole) fiber cloth, poly(arylene oxadiazole) fiber cloth, and ultra-high molecular weight polyethylene fiber cloth.
5. The method for preparing the fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet according to claim 1, wherein: The mixed material in step A2) further includes an inorganic reinforcing component, the mass of which is 0-20% of the sum of the mass of the polyphenylene sulfide powder and the second component colloid; the inorganic reinforcing component is one or a mixture of two or more of carbon black, carbon fiber filaments, carbon nanotubes, silica, zirconium dioxide, boron nitride, silicon nitride, boron carbide, silicon carbide, talc, aluminum oxide, calcium carbonate, etc.
6. The method for preparing a fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet according to claim 1, wherein: The second component colloid is a compound of one or two or more of epoxy resin, silicone resin and phenolic resin; the auxiliary agent includes at least one of a cross-linking agent, an antioxidant and a compatibilizer; the mass of the auxiliary agent is 0.5-5% of the total mass of the blended rubber.
7. The method for preparing a fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet according to claim 1, wherein: The pulverization process in step A1) is one of mechanical pulverization and freeze pulverization; the D50 of the PPS powder after screening is 5-50 μm; the mixing process in step A2) can be one of internal mixing, open mixing, and screw continuous extrusion.
8. A method for preparing a fiber cloth reinforced polyphenylene sulfide alloy composite plate, characterized in that: The following steps are involved: B1) Cutting and stacking prepreg sheets; obtaining a polyphenylene sulfide alloy prepreg sheet according to the method for preparing a fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet according to any one of claims 1 to 7, cutting the polyphenylene sulfide alloy prepreg sheet into a size corresponding to the hot pressing mold using a cutting device, and stacking the prepreg sheets after cutting in 2-1000 layers; B2) Hot lamination: After forming the prepreg sheets, the prepreg sheets are stacked and placed in a hot lamination mold. The lamination equipment temperature is raised to the high temperature range, preheated at a pressure of 0.5-2 MPa for 1-60 minutes, and then hot pressed. The pressure is maintained at a pressure of 2-25 MPa for 10-600 minutes. The high temperature range is 250-350°C. B3) Cooling and cooling; maintaining the molding pressure to cool down, and opening the mold after the temperature drops below 150° C. to obtain a fiber cloth reinforced polyphenylene sulfide alloy composite plate.
9. A fiber cloth reinforced polyphenylene sulfide alloy composite plate, characterized in that: The invention relates to a prepreg material formed by stacking multiple layers of polyphenylene sulfide alloys through a hot lamination method. The hot lamination method comprises stacking multiple layers of polyphenylene sulfide alloy prepreg materials prepared by the method for preparing a fiber cloth reinforced polyphenylene sulfide alloy prepreg material according to any one of claims 1 to 7 and then hot pressing the layers. The hot pressing conditions are: preheating at a high temperature range of 250-350°C at a pressure of 0.5-2 MPa for 1-60 minutes, and maintaining the pressure at a pressure of 2-25 MPa for 10-600 minutes.
10. The fiber cloth reinforced polyphenylene sulfide alloy composite plate according to claim 9 is used in new energy vehicle battery covers, vehicle chassis, and aerospace structural components.
Citation Information
Patent Citations
Preparation apparatus of continuous fiber reinforced thermoplastic resin prepreg tape, and its application
CN102950780A
Manufacture equipment for continuous fiber reinforced thermoplastic composite material and application thereof
CN104723582A
Preparation method of flexible carbon fiber reinforced polyphenylene sulfide composite material laminated plate
CN118721789A
Preparation method of polyphenylene sulfide-based thermoplastic composite prepreg and corresponding prepreg
CN119463247A
Prepreg
JP1996183867A